Design and Construction of Scaffolding with a Lifting Capacity of 300 kg Using a Drive Electric Hoist AC 220 V - Riles Melvy Wattimena; Ignatius Gunawan Widodo; Yuris Bahadur Wirawan; Ahmad Mamba'udin; Abdul Syukur Alfauzi; Bambang Tjahjono; Timotius Anggit Kristiawan; Trio Setiyawan (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Maintenance and repair work in a building or structure is not only in low places, but also in high places which require assistive devices. The assistive device in question is scaffolding. The design of this scaffolding begins with a literature study followed by data collection in the Mechanical Engineering Department of the Semarang State Polytechnic to obtain data on the need for height assistive devices which are used as a reference for making electric scaffolding. The purpose of this study is to design an electric scaffolding with a capacity of 300 kg and to perform the performance of the electric scaffolding made. After the design of the electric scaffolding, the dimensions of the equipment were obtained, namely 1000 mm x 1500 mm x 2000 mm and specifications that can lift goods with a maximum height of 5 m, a minimum height of 0.35 m, a maximum load of 300 kg and an AC 220 V electric hoist drive. Based on the results of the performance test, in this case the test data was taken from the weight of the load that the machine can lift based on the travel time when the machine moves up and down. The load weight of 300 kg with electric scaffolding was covered in 27.44 seconds when going up and 21.02 seconds when moving down.